PEREMPUAN DAN PENDIDIKAN ANAK USIA DINI - Wardana Wardana (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2017)
This paper examines the neighbors of women and early childhood education. Early childhood is a group of children who are in the process of growth and development that is unique, in the sense of having a pattern of growth and development (fine and coarse motor coordination), intelligence (thinking power, creativity, emotional intelligence, and spiritual intelligence), emotional social ( Attitudes and practices and religions), language and communication that are specific to the level of growth and development of children. Early childhood learning activities include aspects, morals, religion, discipline, language ability, thinking power, creativity, emotion, social skills, socializing, and skills. The Role of Women in Early Childhood Education is nurturing; Give birth, nurture and nurture children, teach children about manners based on religious norms. The most influential person in performing character formation is the mother who gave birth to them and PAUD teachers who are generally women.